Design Calculation of Parabolic Trough Solar Thermal System and Three-phaseTurbo Alternator - Theingi Htun; Myo Thet Tun (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Solar energy can be converted into thermal energy with the help of solarcollectors. Electricity can be produced directly from solar energy usingphotovoltaic devices or indirectly from steam generators using solar thermal collectors to heat a working fluid. This research is using the conversion of solar energy into electricity in a closed cycle driven by natural convection. It would mean that electricity is cheaper than from any other renewable technology and cheaper than from fossil fuels. This paper describes converting thermal energy collected by solar collector to electricity by using turbine. Anywhere in Myanmar will cheaply use electricity by using solar turbine generator. Remote areas will improve more and more when getting the efficient electricity. The design calculation and performance predication of 1 MVA turbo-alternator/generator are also mentioned. Design calculation of absorbed flux, useful heat gain and exit temperature is described. And then development of two-tank thermal storage system that uses molten salt as the heat transfer fluid is described.